2005
DOI: 10.1128/iai.73.9.5367-5378.2005
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalisFimbria-Dependent Activation of Inflammatory Genes in Human Aortic Endothelial Cells

Abstract: Epidemiological and pathological studies have suggested that infection with the oral pathogen Porphyromonas gingivalis can potentiate atherosclerosis and human coronary heart disease. Furthermore, infection with invasive, but not noninvasive P. gingivalis has been demonstrated to accelerate atherosclerosis in apolipoprotein E-deficient (ApoE(-/-)) mice and to accelerate local inflammatory responses in aortic tissue. In the present study, using high-density oligonucleotide microarrays, we have defined the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 38 publications
(45 reference statements)
5
70
0
2
Order By: Relevance
“…The reduced cytokine levels in the DPG3-challenged group support several other in vitro studies that have shown that invasive P. gingivalis can induce inflammatory cytokines IL-1␣, IL-1␤, IL-6, and TNF-␣ in gingival fibroblasts, epithelial cells, and macrophages (39 -41). Finally, previous findings indicating that FimA lacking DPG3 is unable to properly produce adhesion molecules involved in cell invasion (34) and only able to up-regulate 4 of 68 up-regulated inflammatory genes by wild-type P. gingivalis in human aortic endothelial cells also suggest a correlation between FimA-dependent cell invasiveness and the pathogenesis of cardiovascular disease (13). Therefore, in addition to the invasion deficiency, DPG3 lacks FimA, a known potent TLR2 ligand, and pathogenicity may be reduced to only LPS (36 -38, 40).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reduced cytokine levels in the DPG3-challenged group support several other in vitro studies that have shown that invasive P. gingivalis can induce inflammatory cytokines IL-1␣, IL-1␤, IL-6, and TNF-␣ in gingival fibroblasts, epithelial cells, and macrophages (39 -41). Finally, previous findings indicating that FimA lacking DPG3 is unable to properly produce adhesion molecules involved in cell invasion (34) and only able to up-regulate 4 of 68 up-regulated inflammatory genes by wild-type P. gingivalis in human aortic endothelial cells also suggest a correlation between FimA-dependent cell invasiveness and the pathogenesis of cardiovascular disease (13). Therefore, in addition to the invasion deficiency, DPG3 lacks FimA, a known potent TLR2 ligand, and pathogenicity may be reduced to only LPS (36 -38, 40).…”
Section: Discussionmentioning
confidence: 97%
“…Porphyromonas gingivalis, which has been strongly associated with adult periodontitis, is a Gram-negative, nonmotile, obligate anaerobe that can invade and infect epithelium, endothelium, and vascular smooth muscle cells (6 -9) and appears to alter endothelial function (10). The capacity for invasion and the subsequent inflammatory responses is in part mediated by fimbriae (11)(12)(13), and the virulence of P. gingivalis may vary among individual strains depending on which one of the five major types of FimA gene they possess (14).…”
mentioning
confidence: 99%
“…The recent findings that fimbriae from P. gingivalis modulated both pro-apoptotic and antiapoptotic genes in human aortic endothelial cells (36) and in gingival fibroblasts (211) confirmed that P. gingivalis could induce either apoptosis or resistance to apoptosis. It appears that the pathway that prevails in a given cell type depends on the balance of cell death and survival modulators that are present.…”
Section: P Gingivalis-induced Resistance To Apoptosismentioning
confidence: 88%
“…Furthermore, there is evidence that P. gingivalis infection may initiate divergent survival and death pathways (36). P. gingivalis fimbriae inhibited growth factor deprivation-induced apoptosis via ERK-dependent expression of p21 in a human monocytic cell line (153).…”
Section: P Gingivalis-induced Resistance To Apoptosismentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] PG�s fimbriae secretes protein, called gp130, [83] which facilitate PG to invade EC and trigger celluler immune response. [84] The host will secrete TNF, [85] IL-1, IL-6, IL-10, and IL-12 [86][87][88] by TLR�s stimulation. [26,85,[88][89][90] TLR is part of immune system, which will respond to PAMP.…”
Section: Discussionmentioning
confidence: 99%